2021
DOI: 10.1208/s12249-020-01897-5
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of 5-Fluorouracil-Loaded Liposomes Containing n-3 Polyunsaturated Fatty Acids in Two Different Colorectal Cancer Cell Lines

Abstract: It has been shown that long-chain n-3 polyunsaturated fatty acids (n-3 PUFAs) could act synergistically with 5-fluorouracil (5-FU) to kill cancer cells. To facilitate their simultaneous transport in the bloodstream, we synthesized, for the first time, liposomes (LIPUFU) containing 5-FU in the aqueous core and docosahexaenoic acid (DHA)/eicosapentaenoic acid (EPA) at a ratio of 1:2 in the lipid bilayer. LIPUFU werestable with uniform size of 154 ± 4 nm, PDI of 0.19 ± 0.03 and zeta potential of -41 ± 2 mV. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…5-FU is an atypical cell cycle-specific drug, which, in addition to acting mainly in the S phase, also has effects on cells in other phases. On the one hand, it blocks DNA replication by inhibiting thymidine synthesis, leading to cell cycle arrest in S phase 50 . A study demonstrated that 5-Fu, an anticancer drug that primarily targets S phase, caused cell cycle arrest in S phase in HCT116 cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…5-FU is an atypical cell cycle-specific drug, which, in addition to acting mainly in the S phase, also has effects on cells in other phases. On the one hand, it blocks DNA replication by inhibiting thymidine synthesis, leading to cell cycle arrest in S phase 50 . A study demonstrated that 5-Fu, an anticancer drug that primarily targets S phase, caused cell cycle arrest in S phase in HCT116 cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, combined enzyme treatment of N. oceanica may be an appropriate high-yield method to extract EPA-rich lipids for use as functional food ingredients or in nutraceuticals and pharmaceuticals. An EPA-rich diet may regulate human immunity [ 48 ], inhibit tumor-cell growth and metastasis [ 49 ], and reduce human triglyceride levels, thus reducing the risk of atherosclerosis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles range in size from between 1 and 1000 nm [7]. Their composition includes phospholipids and other polymeric materials [8]. The size and design of nanoparticles increase the ease at which they permeate tumors, enhancing the deposition of a higher concentration of therapeutic agents in the tumors.…”
Section: Introductionmentioning
confidence: 99%